Activism and Takeovers. (10th April 2021) - Burkart, Mike; Lee, Samuel
Abstract: We compare activism and takeovers from the perspective of a blockholder who can provide effort to improve firm value. We show that free-riding behavior by dispersed shareholders has the following implications: First, activism can be more profitable than a hostile takeover even if it is less efficient. Second, activism is most efficient when it brokers, rather than substitutes for, takeovers. Third, such takeover activism earns superior returns. More broadly, our theory implies that activists specialize in governance reforms with limited, temporary ownership being a strength rather than a shortcoming of activism.